2015
DOI: 10.17576/gema-2015-1501-05
|View full text |Cite
|
Sign up to set email alerts
|

Functional Types of Lexical Bundles in Reading Texts of Malaysian University English Test: A Corpus Study

Abstract: It is widely claimed that many university students were found to be unprepared for the reading demands placed upon them. To provide students with an understanding of the features of the discourses they may encounter, this study investigates lexical bundles (LBs) used in the reading passages of Malaysian University English Test (MUET), a compulsory entrance examination for tertiary education. More specifically it aims to compare and contrast the functional types of LBs found in arts and science-based reading pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…These research-oriented bundles indicate quantities, qualities, or measurements and also describe events. This is consistent with Allen (2009) as well as Beng and Keong (2015), who reported that the most prevalent lexical bundles in their database were those associated with the noun phrases used in academic work.…”
Section: Discussionsupporting
confidence: 89%
“…These research-oriented bundles indicate quantities, qualities, or measurements and also describe events. This is consistent with Allen (2009) as well as Beng and Keong (2015), who reported that the most prevalent lexical bundles in their database were those associated with the noun phrases used in academic work.…”
Section: Discussionsupporting
confidence: 89%
“…With the existence of lexical bundles in reading passages in English books, it can help students understand the reading texts that are given to students. This argument is also supported by Beng and Keong (2015) who state that lexical bundles can help students understand texts. Therefore, students can benefit significantly from the existence of lexical bundles of reading texts.…”
Section: Lexical Bundles Three-word and Four-word In English Textbookmentioning
confidence: 77%
“…At the K-12 level, English language competencies have been found not only to influence students’ socialization patterns affecting learner status (Braden, 2018) but also to restrict their access to and achievement in academic opportunities in the classroom and wider school setting (Ortmeier-Hooper, 2008). After compulsory schooling, entrance-level exams for tertiary education in scientific disciplines often require English language competencies that school-leavers cannot demonstrate (Ong Sook & Chee Keong, 2015), and frustration is common among ESL students who have repeatedly failed English competency exams for science programs (Johns, 1991). For those who are admitted, undergraduate students quickly learn that English language skills, specifically in reading comprehension, summary and paraphrase skills, are vital to their progress (Braine, 1989; Hartshorn, Evans, Egbert, & Johnson, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%